PDGFR-β restores blood-brain barrier functions in a mouse model of focal cerebral ischemia. Issue 8 (August 2019) - Shen, Jie; Xu, Guihua; Zhu, Runxiu; Yuan, Jun; Ishii, Yoko; Hamashima, Takeru; Matsushima, Takako; Yamamoto, Seiji; Takatsuru, Yusuke; Nabekura, Junichi; Sasahara, Masakiyo
Although platelet-derived growth factor receptor beta (PDGFR-β) mediates the recruitment of vascular pericytes into ischemic lesion to restore the blood-brain barrier (BBB) dysfunction, its mechanisms still remain elusive . Compared with control PDGFR-β floxed / floxed mice (Floxed), postnatally induced systemic PDGFR-β knockout mice (Esr-KO) not only showed severe brain edema, neurologic functional deficits, decreased expression of tight junction (TJ) proteins, abundant endothelial transcytosis, and deformed TJs in the BBB, but also showed reduced expression of transforming growth factor-β (TGF-β) protein after photothrombotic middle cerebral artery occlusion (MCAO). In endothelial-pericyte co-culture, an in vitro model of BBB, the increment in the barrier function of endothelial monolayer induced by pericyte co-culture was completely cancelled by silencing PDGFR-β gene expression in pericytes, and was additively improved by PDGFR-β and TGF-β receptor signals under hypoxia condition. Exogenous PDGF-BB increased the expression of p-Smad2/3, while anti-TGF-β1 antibody at least partially inhibited the phosphorylation of Smad2/3 after PDGF-BB treatment in vitro . Furthermore, pre-administration of TGF-β1 partially alleviated edema formation, neurologic dysfunction, and TJs reduction in Esr-KO mice after MCAO. Accordingly, PDGFR-β signalling, via TGF-β signalling, may be crucial for restoration of BBB integrity after cerebral ischemia and therefore represents a novel potential therapeutic target.